Complex Coacervation of Polyelectrolytes Studied by Spin‐Label EPR Spectroscopy. Issue 10 (11th April 2014) - Lappan, Uwe; Wiesner, Brigitte; Scheler, Ulrich
<x xml:space="preserve">Abstract</x> Spin‐labeled poly(ethylene‐alt‐maleic acid) (SL‐P(E‐alt‐MA)) with 2.5 mol% spin‐labeled repeat units is prepared to study the interaction of this polyanion with an oppositely charged polyelectrolyte by electron paramagnetic resonance (EPR) spectroscopy. The internal rotation of the spin label and the segmental rotational mobility of the polyanion in aqueous solution are determined by simulating the line shapes of the experimental EPR spectra as a function of temperature. The complex formation of SL‐P(E‐alt‐MA), a weak polyanion, with the strong polycation poly(diallyldimethylammonium chloride) (PDADMAC) is studied, in dependence of the mixing ratio. If the spin‐labeled polyanion is the excess component, the spectrum of a slow‐moving component is superimposed by the spectrum of a fast‐moving component. In the opposite case, the spectra are dominated by a slow‐moving component. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>